Analisis Efektivitas Time Management Pada PT CBA - Nimas Choirunnisa Safithri; Christian Wiradendi Wolor; Eka Dewi Utari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the effectiveness of time management at PT CBA as a strategy to improve employee productivity and work efficiency. In today’s competitive work environment, effective time management is crucial to achieving goals and completing tasks efficiently. The research applied a quantitative approach through questionnaire distribution to employees and semi-structured interviews with managerial staff. The findings reveal that while most employees are aware of the importance of managing time, implementation is still hindered by internal factors such as discipline, prioritization skills, and external workplace distractions. The study concludes that time management effectiveness at PT CBA falls into the fairly good category but still requires improvement. Recommendations include training programs on time management, enhancing supervisory practices, and developing more structured work systems. These efforts are essential in creating a productive and efficient work culture capable of adapting to operational challenges and supporting the company’s performance targets.